Technological improvement of Zebu cattle breeding efficiency - Mukasa-Mugerwa, E. (Sokoine University of Agriculture, 1987)
This work was conducted to assist the large cattle multiplication centres to produce more animals of the genotype being demanded to improve peasant farm income, to generate an alternative way of introducing the same genotype to farmers with limited income by using artificial insemination, to assist other research projects trying to better understand the reproductive physiology of Zebu cattle and their cross-breds, and to generate basic data on oestrous synchronization. Discusses the physiological basis for controlled breeding, methods used for oestrus induction and synchronization and highlights work on oestrous synchronization in Ethiopian zebu cattle.